The recipient celiac trunk as an alternative to the native hepatic artery for arterial reconstruction in adult liver transplantation. Issue 9 (25th August 2015) - Dokmak, Safi; Aussilhou, Béatrice; Landi, Filippo; Dondéro, Fédérica; Termos, Salah; Paugam‐Burtz, Cathérine; Durand, François; Belghiti, Jacques
<x xml:space="preserve">Abstract</x> During liver transplantation (LT), the recipient hepatic artery (RHA) cannot always be used, and alternatives include aortohepatic conduits and the splenic artery (SA). We report our experience with arterial reconstruction on the recipient celiac trunk (RCT), which has rarely been described. Since January 2013, we have been using the RCT when the RHA could not be used. All cases were discussed in a multidisciplinary LT meeting, and arterial patency or anomalies were systemically viewed with computed tomography (CT) scan. The RCT was used after section‐ligation of all celiac trunk collaterals. Until May 2014, the RHA could not be used in 11/139 (8%) patients who underwent LT. Postoperative arterial patency was assessed by serial Doppler ultrasound and CT scan. The advantages and disadvantages of the different arterial conduits were evaluated. The RCT was used in 7/11 (64%) patients. Mean follow‐up was 10 (6‐15) months. The patency rate was 100%, and 1 patient with associated portal shunting died at day 20 from septic complications. No related gastric or splenic complications were encountered. The RCT could not be used in 4 patients with reconstruction on the SA (n = 2), infrarenal (n = 1), and supraceliac aorta (n = 1). The patency rate was 75%. One patient with SA conduit and portal shunting developed pancreatitis/anastomotic pseudoaneurysm with secondary rupture. An emergency infrarenal conduit was created, which was later embolized because of infected pseudoaneurysms. Although the literature reports a higher risk of thrombosis with aortohepatic conduits, no long‐term results are available for the SA conduits, and only 1 report is available for the RCT. In conclusion, this study shows that the RCT is a good alternative to the RHA and can be used in two‐thirds of patients with inadequate RHA flow. Liver Transpl 21:1133‐1141, 2015. © 2015 AASLD.